1998
DOI: 10.1021/es970900o
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Pyrite Oxidation in Arid Environments

Abstract: Understanding future pit lake water quality has become an important element in permitting open pit mines, due to the potential long-term water quality impacts on ecological receptors. Quantifying pyrite oxidation kinetics is an integral part of this analysis. To date, constraints resulting from low moisture content in the arid regions of the southwestern U.S. that host many large, disseminated deposits have not been considered. In this study, laboratory humidity cells routinely used to simulate pyrite reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…A vuggy texture and intense fracturing of the wall rocks will greatly aid sulfide oxidation. This in turn reduces the solute loads entering the incipient acid pit lake (Fennemore et al 1998). Concentrations of dissolved metals may reach saturation levels.…”
Section: Acid Pit Lakesmentioning
confidence: 99%
“…A vuggy texture and intense fracturing of the wall rocks will greatly aid sulfide oxidation. This in turn reduces the solute loads entering the incipient acid pit lake (Fennemore et al 1998). Concentrations of dissolved metals may reach saturation levels.…”
Section: Acid Pit Lakesmentioning
confidence: 99%
“…Indeed, Hecht and Kölling (2002) performed the complete leaching of the pyrite contained in an unsaturated column of soil consisting of silty sand for a period of around 200 days. Furthermore, Fennemore et al (1998) and Hollings et al (2001) have demonstrated experimentally that the size of the grains, and therefore the specific surface of pyrite, is also a parameter that affects the reactivity of the mineral to oxidation. Fig.…”
Section: The Evolution Of the Solubility Product Of Omentioning
confidence: 99%
“…Water serves as both the reaction medium and as an important reactant (Evangelou and Zhang 1995;Rose and Cravotta 1998). In arid environments, oxidation rates may be 2-3 times lower than rates in humidity cells due to reduced moisture content and larger particle size (Fennemore et al 1998). Sulfur-and iron-oxidizing bacteria can catalyze the kinetic reaction of pyrite oxidation and increase the oxidation rate 30-300 fold (Nordstrom and Alpers 1999).…”
Section: Introductionmentioning
confidence: 99%